Censorship: Social media slowdown (Pakistan) - Voidly (Voidly Global Censorship Index, 2024)
CRITICAL severity censorship detected in Pakistan. Data sourced from CensoredPlanet.
Censorship Incident ID: PK-2024-0004. Severity: critical. Confidence: 75%